The renegotiation of the lomé convention: Experiences and demands - Rolf Hasse; Robert Weitz (Intereconomics, 1978)
Negotiations for an extension of the Lomé Convention of February 28, 1975 (Lomé I) began — almost unnoticed by the public — on July 24, 1978. An analysis of the experiences with the Lomé Convention and the demands and amendments presented by the contracting parties is offered in the following article.
Keywords: 330; EC-ACP